Fuerzas armadas y sociedad - Moncayo Gallegos, Paco, 1940- (Quito : Corporación Editora Nacional, 1995)
"Begins with a historical account of international conflict and the need for national defense. Then discusses the armed forces in Latin America. Concludes with a specific description of the role of the armed forces in Latin America, and in Ecuador in particular. Projects potential roles armed forces could play in the future, such as supporting human rights or protecting the environment"--Handbook of Latin American Studies, v. 57.
Includes bibliographical references (páginas[187]-192).
Descripción basada en recurso en línea; Título de la página del título en PDF (e-libro, visto November 17, 2014).
Recurso electrónico. Santa Fe, Arg.: e-libro, 2015. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a e-libro.
Keywords: Civil-military relations -- Latin America; Relaciones cívico-militares -- América Latina; Civil-military relations -- Ecuador; Relaciones cívico-militares -- Ecuador; Armed Forces -- History; Fuerzas armadas -- Historia; Latin America -- Armed Forces -- Political activity; América Latina -- Fuerzas armadas -- Actividad política.; Ecuador -- Armed Forces -- Political activity; Ecuador -- Fuerzas armadas -- Actividad política.; Libros electrónicos.